Membrane processing of apple juice as an innovative direction in the food industry - Deynichenko, Gregoriy; Дейниченко, Григорій Вікторович; Дмитревський, Дмитро В’ячеславович; Dmytrevskyi, Dmytro; Honchar, D.; Гончар, Д. (Запоріжжя: ТДАТУ, 2025)
EN: The article considers the application of membrane technologies in the production of apple juice as an innovative direction of development of the food industry. A comprehensive analysis of modern membrane processing methods, in particular microfiltration, ultrafiltration, nanofiltration and reverse osmosis, is carried out, which allow to ensure transparency, stability and high organoleptic quality of the product. Special attention is paid to the problem of membrane fouling, which is the main technical challenge in the processing of apple juice, and methods for its minimization are considered, including enzymatic preparation of raw materials, optimization of hydrodynamic modes and the use of ceramic membranes. The analysis shows that membrane processes allow to preserve a high content of biologically active components, such as vitamin C, polyphenols and volatile aromatic substances, and also provide energy savings and a reduction in the use of chemical reagents compared to traditional methods of concentration and clarification. The prospects for integrating membrane stages into combined technological schemes are considered, which contributes to increasing the productivity and quality of the final product. The economic and environmental aspects of the implementation of membrane technologies at industrial enterprises are highlighted. The conclusions of the article indicate that membrane processing of apple juice is an effective and environmentally safe innovative solution capable of ensuring the competitiveness of enterprises and high organoleptic and biological characteristics of the product. /// UA: У статті розглянуто застосування мембранних технологій у виробництві яблучного соку як інноваційно-го та перспективного напряму розвитку харчової промисловості. Проаналізовано основні методи обробки, зокрема мікрофільтрацію, ультрафільтрацію, нанофільтрацію та зворотний осмос, які забезпечують високий рівень прозорості, стабільності та органолептичних властивостей кінцевого продукту, а також сприяють збе-реженню біологічно активних компонентів, зокрема вітаміну C, поліфенолів та летких ароматичних речовин. Особливу увагу приділено проблемі фоулінгу мембран та методам її мінімізації, включаючи ферментативну підготовку сировини, оптимізацію гідродинамічних режимів, застосування поперечного потоку та викорис-тання керамічних мембран. Розглянуто інтеграцію мембранних етапів у комбіновані технологічні схеми, що дає змогу підвищити продуктивність процесу, економічну ефективність виробництва та екологічну безпеку. Доведено, що мембранні процеси забезпечують високу стабільність продукту без використання хімічних реагентів та нагрівання, що дає змогу зберегти натуральний смак, аромат і біологічну цінність яблучно-го соку. Висновки свідчать, що мембранна обробка є ефективним, екологічно безпечним і перспективним рішенням для сучасного виробництва фруктових соків, сприяє підвищенню конкурентоспроможності під-приємств та задоволенню потреб споживачів у високоякісних натуральних продуктах харчування.
Мембранна обробка яблучного соку як інноваційний напрям у харчовій промисловості
Keywords: membrane treatment; apple juice; microfiltration; ultrafiltration; nanofiltration; reverse osmosis; biologically active substances; environmental safety; innovative technologies; мембранна обробка; яблучний сік; мікрофільтрація; ультрафільтрація; нанофільтрація; зворотний осмос; біологічно активні речовини; екологічна безпека; інноваційні технології